La Pista 4’s Cadáveres: Radiophonics and the Argentinean Staging of Disappearance - Graham-Jones, Jean (Latin American Theatre Review, 2010)
Post-dictatorship Buenos Aires performance of disappearance has largely relied upon mimetic embodiment. One striking exception is La Pista 4’s late 1990s Cadáveres, based on six poems by Néstor Perlongher, performed in a wide range of venues, and described in the production handbill as “kind of a radiphonic piece; like one of those we’ll never hear on FM.” In seeking alternatives to representing the absent-yet-present bodies of the disappeared, the production revisited three cultural phenomena of Argentinean redemocratization: postpost- avant-garde poetry, the theatrical staging of disappearance, and FM radio. The result not only materially resituated the performance of disappearance but also constructively responded to the tyranny of the visual in contemporary cultural production. (J G-J, Article in English)